Engineering geological study of the Mai Khola Hyroelectric Project, Ilam, eastern Nepal - Joshi, Pusker Raj; Acharya, Kamal Kant; Dhakal, Rabindra (Journal of Nepal Geological Society, 2018)
The Mai Khola Hydroelectric Project, a run-of-river scheme, has a capacity 15.6 MW. It has design discharge of 16 m3/s, design net head of 112.71 m and includes 2192 m long inverted-D shaped headrace tunnel with 4.3 m diameter, concrete dam of 10.6 m height and semi-surface powerhouse. The project area consists of rocks of the Middle Siwalik Subgroup, comprising of sandstone, siltstone and mudstone, inter bedded frequently. Sandstone is predominant in head works area, headrace tunnel and is completely absent in a surge tank, and penstock alignment. Siltstone alternating with thin layer of mudstone is predominant in powerhouse area. The headrace tunnel outlet portal and surge shaft lie on the hill slope characterized by colluvial deposits. The penstock alignment passes through highly weathered siltstone and mudstone. The semi-surface powerhouse and the tailrace canal lie on the lower alluvial terrace. The Main Boundary Thrust (MBT) is the major structure observed at about 90 m upstream from the weir axis. The average Q-value of rock mass along the headrace tunnel surface mapping was 0.062–1.33 and after excavation the value was 0.004–0.23. An extremely poor to poor relation was observed between the rock mass class on surface mapping and exceptionally poor to very poor on excavation. Analysing the results of the surface and underground study of the rock mass, the excess support is required during construction.